2010
DOI: 10.1155/2010/568343
|View full text |Cite
|
Sign up to set email alerts
|

Role of Leptin in the Activation of Immune Cells

Abstract: Adipose tissue is an active endocrine organ that secretes various humoral factors (adipokines), and its shift to production of proinflammatory cytokines in obesity likely contributes to the low-level systemic inflammation that may be present in metabolic syndrome-associated chronic pathologies such as atherosclerosis. Leptin is one of the most important hormones secreted by adipocytes, with a variety of physiological roles related to the control of metabolism and energy homeostasis. One of these functions is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
288
0
13

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 356 publications
(312 citation statements)
references
References 72 publications
11
288
0
13
Order By: Relevance
“…In vitro neutralization with a leptin monoclonal antibody during stimulation with anti-CD3 and anti-CD28 antibodies resulted in Treg proliferation, which was IL-2 dependent. 36,58 These findings indicate that leptin signaling is clearly involved in maintaining the anergic state of human Tregs. In agreement with this, both leptindeficient (ob/ob mice) and leptin receptor-deficient mice (db/db mice) were associated with a marked increase in the number of Tregs (Figure 3).…”
Section: Leptin and Autoimmunity M Vadacca Et Al 205mentioning
confidence: 77%
See 4 more Smart Citations
“…In vitro neutralization with a leptin monoclonal antibody during stimulation with anti-CD3 and anti-CD28 antibodies resulted in Treg proliferation, which was IL-2 dependent. 36,58 These findings indicate that leptin signaling is clearly involved in maintaining the anergic state of human Tregs. In agreement with this, both leptindeficient (ob/ob mice) and leptin receptor-deficient mice (db/db mice) were associated with a marked increase in the number of Tregs (Figure 3).…”
Section: Leptin and Autoimmunity M Vadacca Et Al 205mentioning
confidence: 77%
“…The primary amino acid sequence of leptin indicated that it could belong to the long-chain helical cytokine family, 36,42 with members such as IL-2 and IL-12. The cytokine-like structural characteristic of leptin is implicative of its function in regulating immune response.…”
Section: Leptin Inflammation and Immune Responsementioning
confidence: 99%
See 3 more Smart Citations